Chemical route synthesis dependent particle size of Mn activated ZnS nanophosphors. (25th January 2011) - Sharma, Ravi; Dhoble, S.J.; Bisen, D.P.; Brahme, Nameeta; Chandra, B.P.
The synthesis and optical properties of Mn activated ZnS nanoparticles are reported in this paper. Nanoparticles of zinc sulphide were prepared by chemical route technique; whereas mercaptoethanol (ME) was used as the capping agent. The particle size of such nanocrystals was measured using XRD, SEM and TEM patterns and was found to be in between 3 nm to 5 nm. The blue-shift in the absorption spectra was found with reducing size of the nanoparticles. It was also found that the change in Mn concentrations does not influence the particle size and blue-shift in the absorption spectra. The optical absorption edge was found at 296 nm for all the doped samples for fixed concentration of capping agent. The particle size of nanoparticle was calculated both theoretically and experimentally, which is nearly the same. The FTIR spectra inferred that the stabilising agent passivates the surface of the particles.